Challenges and Pitfalls in the Engineering of Human Interleukin 22 (hIL-22) Secreting Lactobacillus reuteri - Ortiz-Velez, Laura; Goodwin, Annie; Schaefer, Laura; Britton, Robert A. (Frontiers in Bioengineering and Biotechnology, 2020)
Engineered microbes for the delivery of intestinally directed therapeutics is a promising avenue for the treatment of various intestinal diseases including inflammatory bowel disease (IBD) and intestinal graft versus host disease (GVHD). This modality of treatment would allow for the targeted delivery of therapeutics to the site of inflammation or disease while minimizing the systemic side effects that often accompany treatment of these pathologies. Here, we show the challenges and pitfalls encountered and overcome in successfully engineering Lactobacillus reuteri to secrete high levels of biologically active human interleukin 22 (hIL-22). Our work highlights the complexities involved in the engineering of bacteria for therapeutic delivery and serves as a significant step forward in the engineering of commensal organisms, like Lactobacillus reuteri, as a biotherapeutic delivery system.